Facial expression recognition under difficult conditions: A comprehensive study on edge directional texture patterns - Ahmed, Faisal; Kabir, Md. Hasanul (Zielona Góra: Uniwersytet Zielonogórski)
In recent years, research in automated facial expression recognition has attained significant attention for its potential applicability in human-computer interaction, surveillance systems, animation, and consumer electronics. However, recognition in uncontrolled environments under the presence of illumination and pose variations, low-resolution video, occlusion, and random noise is still a challenging research problem.
Keywords: directional ternary pattern; compressed DTP; facial feature descriptor; texture encoding; support vector machines